Intimate partner violence against women of reproductive age and associated factors during COVID-19 pandemic in Northern Ethiopia, 2021: A community-based cross-sectional study - Demeke, Mekasha Getnet; Shibeshi, Ehtemariam Tefera (Frontiers in Global Women's Health, 2023)
Abstract Background: Intimate partner violence (IPV) is a major public health concern that affects more than one-third of all women globally. Assessing the prevalence and associated factors of Intimate Partner Violence during Covid-19 pandemics in various localities is crucial for intervention actions. So far, a few studies were done in Ethiopia during the current Covid-19 pandemics. Objective: This study was aimed to assess the prevalence and associated factors of Intimate Partner Violence during the Covid-19 pandemic among women of reproductive age in Debre Berhan town, Ethiopia, 2021. Methodology: A community based cross-sectional study was done. A total of 809 ever-partnered women of reproductive age were selected randomly via multistage sampling method. Crude (COR) and adjusted odds ratios (AOR) with the resulting 95% confidence interval (CI) were used to verify strength of associations. Significant associations were declared at p-values <0.05. Result: Among the 796 women who successfully participated in the study, 337(42.3%) experienced at least one type of Intimate Partner Violence. Prevalence of psychological, physical, and sexual violence was 281(35.3%), 122(15.3%) and 121(15.2%), respectively. Multivariate analysis revealed that women with no formal education (AOR, 95% CI 3.66(1.91, 6.98)), having no own income (AOR, 95% CI 1.78(1.24, 2.56)), and attitude of IPV is acceptable (AOR, 95% CI 4.02(1.33, 12.14)); a male partner with no formal education (AOR, 95% CI 3.06(1.53, 6.14)), with ‘level of religious beliefs’ (weak (AOR, 95% CI 4.17(1.45, 12.03); and medium (AOR, 95% CI 1.64(1.13, 2.39)), alcoholics (AOR, 95% CI 5.91(4.03, 8.67)), and smoking habits (AOR, 95% CI 2.04(1.10, 3.77)) and >5 (AOR, 95% CI 1.83(1.01, 3.39)) were significantly associated with the presence of Intimate Partner Violence. Conclusion and recommendation: This study revealed that there was a high prevalence of IPV among the study participants. The high Intimate Partner Violence prevalence was due to multiple factors, thus demanding empowering the women and tailored health education to male-partners.